Inhibition of Autophagy Prolongs Recipient Survival Through Promoting CD8+ T Cell Apoptosis in a Rat Liver Transplantation Model - Chen, Xiaolong; Wang, Li; Deng, Yinan; Li, Xuejiao; Li, Guolin; Zhou, Jing; Cheng, Daorou; Yang, Yang; Yang, Qing; Chen, Guihua; Wang, Genshu (Frontiers in Immunology, 2019)
In liver transplantation (LT), although various immunosuppressants have been used in clinical practice, acute rejection remains a common complication that significantly shortens recipient survival. In recent years, manipulating immune tolerance has been regarded as one of the promising solutions to rejection. Autophagy, an evolutionarily conserved protein degradation system, has been reported to be involved in immune rejection and may be a target to establish immune tolerance. However, the role of autophagy in acute rejection reaction after LT has not been elucidated. Here, we showed that the autophagy of CD8+ T cells was strongly enhanced in patients with graft rejection and that the autophagy level was positively correlated with the severity of rejection. Similar findings were observed in a rat acute hepatic rejection model. Furthermore, administration of the autophagy inhibitor 3-methyladenine (3-MA) largely decreased the viability and function of CD8+ T cells through inhibiting autophagy, which significantly prolonged graft survival in rats. In addition, inhibiting the autophagy of activated CD8+ T cells in vitro considerably suppressed mitochondria mediated survival and downregulated T cell function. Conclusions: We first showed that the inhibition of autophagy significantly prolongs liver allograft survival by accelerating the apoptosis of CD8+ T cells, which will provide a novel strategy for immune tolerance induction.